The victim matters: Experimental evidence on lying, moral costs and moral cleansing - Lukas Meub; Till Proeger; Tim Schneider; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
In an experiment on moral cleansing with an endogenously manipulated moral self-image, we examine the relevance of the addressee of an immoral action. The treatments differ such that cheating on a die roll reduces either the experimenters or another subjects payoff. We find that cheating is highest and moral cleansing lowest when subjects cheat at the expense of the experimenter, while cheating is lowest and moral cleansing highest once cheating harms another subject. A subsequent measurement of subjects moral self-image supports our interpretation that the occurrence of moral cleansing crucially depends on the moral costs resulting from immoral actions directed at individuals in different roles. Our results can help to explain the different propensity to cheat and conduct moral cleansing when immoral actions harm either another person or the representatives of an organization.
Keywords: C91; D1; 330; dictator game; laboratory experiment; lying; moral balancing; moral; cleansing; self-image